Les parapluies de Cherbourg - Legrand, Michel 1932-2019 (Intégrale Jacques Demy, 2008)
Set in the French seaside town of Cherbourg, the all-sung dialogue tells of the relationship between shopgirl Geneviève who discovers that she is pregnant after her garage mechanic boyfriend, Guy, is drafted to fight in the Algerian war. She marries Roland Cassard, but lives with the knowledge that her true love lies elsewhere